Rapid access rather than open access leads to improved effectiveness of an ENT emergency clinic. Issue 1 (2nd October 2013) - Smyth, Catherine; Moran, Michael; Diver, Catherine; Hampton, Susanne
Abstract: An Ear, Nose and Throat (ENT) emergency clinic provides important access to specialist care for patients referred by General Practitioners (GPs), Emergency Departments and doctors on non-ENT hospital wards. The aim is to enable the prompt diagnosis and management of acute conditions, within an optimum environment containing appropriate clinical and staff resources. Amid concerns that an open access ENT casualty service had become overburdened we performed a four week audit of all attendances. We identified 45% of patients presenting to the clinic without having evidence of first accessing primary care assessment or treatment. Waiting times were unpredictable, averaging 75 minutes and clinic numbers above those recommended to be safe in national guidelines. 60% of attendances to the department were judged to be inappropriate. Subsequently the ENT emergency service was changed to an appointment based Rapid Access Clinic, with an easily accessible and prompt triage facility provided by a trained triage nurse. Concurrently the opportunity was taken to improve record keeping and formalise post consultation communication. Re-audit confirmed a 43% reduction in the number of patients accessing the ENT emergency clinic facility, allowing individual clinic numbers to fall to safe levels. Average patient waiting times fell by 70% to 22 minutes. The number of referrals judged to be inappropriate was halved. The transformation of our service has enabled time and resources to be more effectively directed towards a smaller number of patients, whose needs are more urgent.